The burning answer : the solar revolution : a quest for sustainable power - Barnham, Keith, 1943- (Pegasus Books, 2015)
Our civilization faces a choice. We could be enjoying a sustainable lifestyle but we have chosen not to. In three generations we have consumed half the oil produced by photosynthesis over eight million generations. In two generations we have used half our uranium resources. With threats from global warming, oil depletion and nuclear disaster, we are running out of options. Solar power, as Keith Barnham explains, is the solution. In THE BURNING ANSWER he uncovers the connections between physics and politics that have resulted in our dependence on a high-carbon lifestyle, which only a solar revolution can now overcome. Einstein's famous equation E=mc2 led to the atomic bomb and the widespread use of nuclear energy; it has delayed a solar revolution in many countries. In a fascinating tour of recent scientific history, Keith Barnham reveals Einstein's other, less famous equation, the equation the world could have relied on. Einstein's other equation has given us the laptop and mobile phone, and it also provides the basis for solar technology. Some countries have harnessed this for their energy needs, and it is not too late for us to do the same. In this provocative, inspiring, passionately argued book, Keith Barnham outlines actions that any one and all of us can take to make an impact now and on future generations. THE BURNING ANSWER is a solar manifesto for the new climate-aware generation, and a must-read for climate-change sceptics.